The Association Between Antibiotic Use and Outcome Among Metastatic Melanoma Patients Receiving Immunotherapy. (7th March 2022) - Poizeau, Florence; Kerbrat, Sandrine; Balusson, Frédéric; Tattevin, Pierre; Revest, Matthieu; Cattoir, Vincent; Luque-Paz, David; Lesimple, Thierry; Pracht, Marc; Dinulescu, Monica; Russo, David; Oger, Emmanuel; et al.
Abstract: Background: Several observational studies have reported a decreased response to immune checkpoint inhibitors (ICI) following antibiotic use. ICI activity has been hypothesized to be impaired by antibiotic-induced gut dysbiosis. Methods: Patients with advanced melanoma receiving an anti-PD-1 antibody as a first-line therapy between 2015 and 2017 in France were selected using the French Health Insurance database. We compared overall survival and time-to-treatment discontinuation according to antibiotic exposure in the 3 months prior to the initiation of anti-PD-1 antibody. To disentangle a causal effect of antibiotics from a confounding bias, we balanced characteristics of patients exposed and nonexposed to antibiotics using an overlap weighting method based on a propensity score. We also evaluated a control cohort of patients with advanced melanoma receiving first-line targeted therapy, as there is no rationale for decreased efficacy of targeted therapy following antibiotic treatment. Results: The anti-PD-1 antibody cohort comprised 2605 individuals. Antibiotic exposure in the 3 months prior to anti-PD-1 antibody initiation was not associated with shorter overall survival (weighted hazard ratio = 1.01, 95% confidence interval = 0.88 to 1.17) or time-to-treatment discontinuation (weighted hazard ratio = 1.00, 95% confidence interval = 0.89 to 1.11). Consistent results were observed when the time frame of antibiotics was narrowed to 1 month prior to anti-PD-1 initiation or when exposure was restricted to antibiotics leading to more profound gut dysbiosis. Similar results were observed in the targeted therapy cohort. Conclusions: In a large cohort of advanced melanoma patients, we showed that antibiotic use preceding anti-PD-1 antibody was not associated with worse outcome. Physicians should not delay immunotherapy for patients who have recently received antibiotics.